THE ROLE OF SQUAT EXERCISE IN MEDICAL PRACTICE: EVIDENCE AND CLINICAL APPLICATIONS - Michał Wabiszczewicz; Albert Lompart; Albert Kosarewicz; Łukasz Woźniak; Patrycja Krysiak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective: The squat is a fundamental human movement and widely used exercise with recognized importance in sports, rehabilitation, and preventive medicine. This narrative review aims to summarize current evidence (2020–2025) on the medical impact of squat exercise across diverse populations, emphasizing musculoskeletal, skeletal, cardiovascular, and functional outcomes.Review Methods: A structured search was conducted in PubMed, PLOS One, Wiley, and JSTOR for articles published between January 2020 and February 2025. Inclusion criteria were peer-reviewed human studies addressing health-related effects of squat exercises. Exclusion criteria included animal studies, conference abstracts, and articles focusing solely on athletic performance. Approximately 30 key studies were analyzed narratively.State of Knowledge: Evidence indicates that squat training improves muscle strength, hypertrophy, and bone mineral density, with quadriceps showing the largest force gains (~18%). Cardiovascular and metabolic adaptations include improved oxygen consumption, blood pressure regulation, and postprandial glucose control. Functional benefits extend to older adults, where squats enhance sit-to-stand capacity and daily mobility, and to special populations such as pregnant women, where squats reduce fatigue and improve quality of life. Variations in depth, load, and technique influence outcomes and safety.Summary: Squat exercise represents a versatile intervention with significant health benefits across age groups and clinical conditions. Incorporating squats into individualized exercise prescriptions may help prevent osteoporosis, sarcopenia, cardiovascular disease, and functional decline, reinforcing its role in evidence-based medical and rehabilitation practice.